Geochemistry and tectonic setting of Paleogene volcanic rocks of Rudbar in the south of Guilan, northern Iran: Implications for adakitic volcanism - Esmail Ebrahimi nasirmahaleh; Mojgan Salavati; Saeid Hakimi Asiabar; Saeed Taki (پترولوژی, 2023)
IntroductionVolcanic rocks with adakitic nature, are outcropped, in the south of Rudbar city as a part of the Alborz magmatic zone and the northern part of the Alborz zone. Most of the rock units in this area are volcanic and pyroclastic belonging to the Tertiary age and specifically Middle Eocene.For this study, we present new data to understand the origin and tectonic setting of the adakitic early Cenozoic magmatism in the southern part of the western Alborz orogenic belt.Regional GeologyBased on the 1:100,000 Guilan geological map (Nazari and Salamati, 1998), the predominant geological units of the region include the Paleozoic, Mesozoic, and Cenozoic stratigraphic units. The volcanic activity resulting from the subduction of an oceanic crust beneath the active continental margin of Alborz began in Paleocene and its peak is attributed to the Lutsin period (Nazari and Salamati, 1998).Materials and methods Following microscopic studies, 11 samples were analyzed at Actlabs Lab in Canada by ICP-MS method. IGPET and GCDKIT software were applied to draw diagrams and interpret the data.Petrography and Whole rocks chemistry The studied lavas consist mainly of dacite to trachy-dacite, rhyodacite, and rarely rhyolite. Abundant plagioclase as phenocrysts and microlites and rare amphibole, biotite, and quartz with hyaloporphyritic, microlithic porphyry to felsitic porphyry and microfelsitic textures are the dominant petrographic features of these rocks. Geochemically, they are characterized by mean value of 61.87 wt%< SiO2<66.54, 1.1 wt%<MgO<2.8 wt%,10 ppm<Y<14 ppm, 1.4 ppm<Yb<1.7 ppm, 450 ppm<Sr<1887 ppm as well as the average amounts of Sr/Y: 103.8, 10.5<(La/Yb)N<14.09 and 5.1<Yb/Lu<6.5. Thus, the overall geochemical data point to HAS characteristics of the rocks under study. On normalized spider diagram to chondrite, MORB, and primitive mantle, all rocks demonstrate subparallel trend, linear and homogeneous REE profiles with LILE and LREE enrichment together Ta, Nb, and Ti negative anomalies. As the tectonic diagrams display, all the studied samples are plotted in an arc volcanic granite field formed in a subduction environment in an active continental margin. Moreover, all the obtained geochemical data point to a high silica adakitic magma as the parent magma.DiscussionThe studied area lies in Alborz Mountain, which owing to the collision of two Eurasian and Arabian plates, where a Neo-Tethyan oceanic lithosphere (Southern Caspian Sea Ocean or SCO)” is subducted beneath the Central Iranian continental lithosphere (Salavati et al, 2013), is an active deformation zone.The studied rocks formed in arc and subduction zones setting. Adakitic rocks in the arc setting can be produced by partial melting of a hot and young subducted oceanic slab and subduction of a very young oceanic crust (<5Ma) at depths of about 25 to 90 km is required to produce adakitic magma in the arc setting (Thorkelsona and Breitsprecher, 2005).In the north of the investigated area and south part of the Caspian Sea, an Alpian oceanic belonging late Cretaceous age was reported and named “Southern Caspian Sea Ocean (Salavati et al., 2013), which was subducted toward the south. Adakitic activity and not-adakitic magmatism continued to migrate toward the trench supporting a slab window model.The proposed tectonomagmatic model "Ridge-Trench", indicates that the studied lavas were generated in the Neothetyan supra-subduction zone.Based on this model, in the south of Guilan Province, SCO oceanic crust (and likely its ridge) has subducted towards the south the first because of a pressure change that might be caused by the extension and thinning of the overlying crust. A slab window was formed therefore in the source region, and partial melting occurred by asthenospheric upwelling. It looks like the adakitic rocks imply a deep source with a low magma source melting degree.ConclusionThe overall petrological and geochemical features of the studied lavas gave rise to the following conclusions:A new group of extrusive rocks, with remarkable geochemical characteristics of adakitic rocks, is outcropped in the south of Guilan ProvinceThese rocks are characterized by HFSE and HREE depletion relative to LILE and LREE and negative Nb, Ta, and Ti anomalies, suggesting the parent magmas were affected by subduction-related geochemical processes.On tectonic diagrams, the studied adakitic rocks plotted on an Active Continental Margin setting and they show HAS characteristics produced by 5% to 10% partial melting of an amphibolite garnet source from a hot and young Cenozoic slab subduction.All the geological and geochemical data indicate that the early Cenozoic adakitic magmas in the south of Guilan Province were generated in an extensional tectonic setting (Slab window setting) when the active spreading center of the Neo-Tethys oceanic (Southern Caspian Sea Ocean) subducted toward the south and produced a slab window. According to the proposed model, the active spreading center of the Neo-Tethys oceanic crust (Southern Caspian Sea Ocean) subducted toward the south and produced a slab window in the subducted oceanic lithosphere.AcknowledgmentsWe appreciate the Office of Graduate Studies of Islamic Azad University, Lahijan Branch.